In situ polymerisation of isoeugenol as a green consolidation method for waterlogged archaeological wood - McHale, Emily; Steindal, Calin C.; Kutzke, Hartmut; Benneche, Tore; Harding, Stephen E. (Nature Publishing Group, 2017)
Waterlogged archaeological wood is often in need of consolidation prior to drying to prevent shrinkage and cracking of the object. There is a need for new greener materials (than for example polyethylene glycol) and methods for consolidation to be developed. The use of wood-based components could provide good interaction between the consolidant and the remaining wood structure and would also support a shift away from fossil fuel-based materials to those with more sustainable sources. Based on this, lignin-like structures have been investigated for their ability to consolidate waterlogged archaeological wood. The in situ formation of a lignin-like material has been carried out using isoeugenol polymerised by horse radish peroxidase in aqueous solution. The formation of the oligomeric/polymeric materials within the wood following this reaction has been determined by Attenuated Total Reflectance Fourier Transform Infra Red (ATR-FTIR) spectroscopy. The oligomers remaining in solution have been characterised by ATR-FTIR and nuclear magnetic resonance (NMR) spectroscopy as well as analytical ultracentrifugation, showing that they have a weight average Mw of 0.4–0.9 kDa and a lignin-like structure rich in the β-5′ moiety. Therefore, this approach is proposed as a basis to further develop a green consolidation method for waterlogged archaeological wood.